The Chain of Tafsir Scholars Transmission Network in Nusantara - Arief, Armai (International Journal of Psychosocial Rehabilitation, 2020)
This study will portrait the chain of tafsir (exegesis) scholars network transmission in Nusantara ranging. We have recorded the networks of Hijaz or Haramayn connection that is now in Saudi Arabia, Egyptian connection through al-Azhar University or Azhari lines, Indian subcontinent of India and Pakistan in nowadays, and even western connection through the students who studied in the western universities either Europe or America prior to 20th century until recently study. The style and the typology of the archipelago’s Tafsir cannot be separated from the transmission of the tradition of Tafsir of the Hijazi, Azhari, Indian Sub-continent, and Western scholars. Hijazi, here means the transmission of writing, thought and Tafsir traditions that developed in Mecca and Medina. Then, the Tafsir of the archipelago also has the connectivity and the strong attachment with the mindset of al-Azhar of Egypt that gave birth to many scholars in the archipelago that indirectly or directly contributed to the archipelago exegesis. More ever, Hijazi and Azhar are more viscous sticking of the exegesis in the sixteenth century until the early twentieth century here.